Glocalized rhetoric practices on medical writing - Lu 盧慧娟 Hui-Chuan; Tsou 鄒文莉 Wenli; Chen 陳慧琴 Fay (Círculo de Lingüística Aplicada a la Comunicación, 2017)
Facing a rapidly changing global environment, educators around the world have argued for a need to incorporate a global perspective in local educational policy making. The present study undertakes such a glocal project examining medical writing of international physicians and Taiwanese interns. In this study, the Corpus of English for Medical Purpose (CEMP) has been created. There are 50 experts’ (49,655 words) and 50 students’ (9,829 words) medical writing samples respectively. The moves and steps used between the two groups were analyzed from three linguistic features, voice form, tense, and grammatical subject. Then, a parallel corpus was consulted in an attempt to explain the rhetoric features unique to Taiwanese writers. Based on the findings, a framework is proposed to provide guidance for the instruction and learning of medical writing. The findings contribute to medical education by highlighting how the dual forces of the target and native languages shape students’ medical writing.